Mongolian mining engagement with SIA and ESG initiatives - Sternberg, T.; Ahearn, A. (Environmental Impact Assessment Review, 2023)
The shift to a low-carbon future places mineral-rich low- and middle-income countries at the forefront of the green transition. The focus on investment and extraction presents significant domestic challenges as countries endeavour to create viable development agendas. Framed by initiatives including environmental, social and governance (ESG), impact assessment (IA) and Sustainable Development Goals (SDGs), the international com- munity works to improve extractive practices. In Mongolia, the most mining-dependent country in Asia, addressing and mitigating industry impacts is key to continued resource extraction and economic progress. Whilst often a signatory to global programmes, government engagement is limited. Mongolia ranks 157th in ESG and though mining licenses cover 4% of the country, there is no social impact assessment (SIA) legislation. Extensive research on the development of SIA guidelines identified strong community interest yet dilatory official uptake and commitment. Ongoing engagement with civil society has seen regulations advanced and the legislative process initiated. Mongolia’s struggle identifies common challenges LMICs face in the implementation of global initiatives. Whilst well-intentioned, without government commitment ESG and IA will remain ambiguous terms for serious social and environmental issues in mining nations.